(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Aim: To determine tear mucin levels in patients with type 2 diabetes mellitus (T2DM) and correlate them with the levels of the neutrophil activation marker CD15+ in epithelial cells of the bulbar conjunctiva in patients with T2DM, depending on the grades of squamous metaplasia. Material and Methods: Thirty-seven patients (37 eyes) with ocular surface damage and T2DM comorbidity were enrolled in this study. Fifteen sex- and age-matched participants without T2DM comprised the control group. Based on the cytological changes in the bulbar conjunctiva and according to Nelson’s classification, patients with T2DM were divided into two main groups: Study group 1 – 29 patients (29 eyes) with changes in the bulbar conjunctiva corresponding to grades II and III of squamous metaplasia according to Nelson’s classification; study group 2 – 8 patients (8 eyes) with grades 0-I according to Nelson’s classification. Results: The mucin level was significantly lower in study group I - 0.95 ± 0.18 g/l compared to study group II - 1.28 ± 0.09 g/l and controls - 1.59 ± 0.08 g/l (p<0.0001). Median relative expression of CD15+ was 4 % in study group I whereas only one patient in study group II (12.5 %) and the control group (6 %) was positive for CD15+ expression. Relative expression of CD15+ strongly negatively correlated with the mucin level in the study group I (rs = -0.87; p ˂ 0.0001). Nelson’s grades also negatively correlated with mucin levels in patients with T2DM (rs = -0.87; p˂0.0001). Conclusion: Tear mucin levels are significantly reduced in patients with T2DM and show a strong negative correlation with the neutrophil activation marker CD15+ in the epithelial cells of the bulbar conjunctiva depending on the grade of squamous metaplasia. This indicates dysregulation of ocular surface homeostasis and the inflammatory component in the development of ocular surface damage in T2DM.